2015
DOI: 10.1111/ajt.13027
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Complications After Liver Transplantation for Propionic Acidemia in Children: A Two Centers Study

Abstract: Propionic acidemia (PA) is a severe metabolic disorder with cardiac and neurologic complications and a poor quality of life. Liver transplantation (LT) was thus proposed in PA to increase enzyme activity. We studied retrospectively LT in PA in two European centers. Twelve patients underwent 17 LTs between 1991 and 2013. They developed severe, unusual and unexpected complications, with high mortality (58%). When present, the cardiomyopathy resolved and no acute metabolic decompensation occurred allowing dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 23 publications
4
100
1
1
Order By: Relevance
“…A recent report from the Withdrawal of Immunosuppressants in Pediatric Liver Transplant Recipients (WISP-R) trial confirmed the benefits in renal function in 12 tolerant pediatric liver transplant recipients, of whom eight were withdrawn from tacrolimus-based immunosuppressant therapy [28]. In addition, two European centers demonstrated that renal function decline is a major concern in long-term follow-up pediatric recipients transplanted for propionic acidemia (an inborn error in organic acid metabolism) [29], which was favorable to achieve COT in our study (including one patient with propionic acidemia and two patients with methylmalonic acidemia). As immunosuppressant carries life-long risk to our pediatric liver transplant recipients, our results may be implicating a new strategy toward early immunosuppressant minimization in these patients to achieve better long-term outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…A recent report from the Withdrawal of Immunosuppressants in Pediatric Liver Transplant Recipients (WISP-R) trial confirmed the benefits in renal function in 12 tolerant pediatric liver transplant recipients, of whom eight were withdrawn from tacrolimus-based immunosuppressant therapy [28]. In addition, two European centers demonstrated that renal function decline is a major concern in long-term follow-up pediatric recipients transplanted for propionic acidemia (an inborn error in organic acid metabolism) [29], which was favorable to achieve COT in our study (including one patient with propionic acidemia and two patients with methylmalonic acidemia). As immunosuppressant carries life-long risk to our pediatric liver transplant recipients, our results may be implicating a new strategy toward early immunosuppressant minimization in these patients to achieve better long-term outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Those without liver diseases will be more vulnerable to acute metabolic decompensation due to the transplant procedure itself, which, in turn, may impact early allograft function. Higher rates of early graft dysfunction, hepatic artery thrombosis, and perioperative systemic complications are recognized in those with nonstructural disease …”
Section: Discussionmentioning
confidence: 99%
“…Some individuals have received liver transplants to treat PA and liver, kidney, or combined liver-kidney to metabolically stabilize MMA and/or address the chronic renal failure associated with MMA disease [12, 18, 24, 60, 196, 201, 217239]. Liver transplantation has become an increasingly popular treatment choice for children with more severe or brittle disease, and some adults undergo isolated kidney transplant for MMA-related end-stage renal disease.…”
Section: Transplantmentioning
confidence: 99%
“…One center has claimed that liver transplantation is more cost-effective than dietary therapy alone [228]. Not all sequelae of PA and MMA may be prevented by liver transplantation; some liver-transplanted patients have developed metabolic stroke after transplant and others have had progressive vision loss due to optic atrophy as well [18, 231, 232, 236, 239, 240]. Further studies on the long-term outcomes of transplantation and changes to the natural history of disease are indicated.…”
Section: Transplantmentioning
confidence: 99%